Impacts of test methods on the assessment of insulation materials' resistance against moulds. (15th July 2020) - Tobon, Ana Maria; Andres, Yves; Locoge, Nadine
Abstract: Bio-based insulation materials have been increasing in the construction market, however, these materials must prove their resistance to moulds. This research project aimed to compare two test methods to assess the resistance against moulds of two bio-based insulation panels and a mineral conventional panel artificially contaminated with Aspergillus niger spores. Test specimens were assessed applying a reference test method and a method developed in this work. The two methods consisted in four steps: 1) preconditioning of test specimens at 26 °C and 85 ± 5% of relative humidity during 1 week, 2) inoculation of test specimens, 3) incubation of test specimens at 26 °C and 85 ± 5% of relative humidity during four weeks and, 4) growth assessment by visual inspection and CFU counting. The difference between the methods is the contamination technique, which is a liquid inoculum for the reference method and a dry aerosolization of fungal spores for the new method. A dry aerosol was used because is a more realistic way on how materials get contaminated in realistic conditions and avoids the introduction of water into the system and in consequence, the modification of water activity (Aw). Materials presented different behaviours concerning visual and quantitative assessments according the test method employed, highlighting the difficulty establishing a standard test method to assess bio-based materials resistance to mould growth. The results showed that an evaluation only by a visual inspection may lead to misinterpretations of the results. Variability in the results may have been due to the differences in the inoculation techniques of the test methods and the heterogeneity of the materials composition and the anti-fungal product distribution within them. Highlights: Bio-based insulation materials may respond differently to mould growth. An inoculation method using a liquid inoculum may alter water activity. Dry aerosolization of spores is a more realistic method to contaminate test specimens. Mould growth assessment by visual inspection may lead to misinterpretations of the results.